Diagnostic and Prognostic Potential of Circulating HSP70 and GRIN2B in Primary Open-Angle Glaucoma - Nedilka , Taras; Lutsenko , Nina (The Ukrainian Scientific Medical Youth Journal, 2025)
Primary open-angle glaucoma is increasingly recognized as a multifactorial neurodegenerative disease in which the progression of optic nerve damage is driven not only by elevated intraocular pressure but also by disturbances in vascular regulation, metabolic imbalance, oxidative stress, and glutamate-mediated excitotoxicity. These mechanisms create the need to identify circulating biomarkers capable of reflecting early and ongoing injury of retinal ganglion cells. The HSP70 is considered an indicator of cellular stress and a potential mediator of endogenous neuroprotection, while the NR2B subunit of the glutamate receptor, encoded by the GRIN2B gene, is involved in excitotoxic neuronal damage. The present study investigated the plasma concentrations of these two markers in individuals with primary open-angle glaucoma and healthy participants, as well as their dynamics after a short course of neuroprotective therapy consisting of reduced glutathione and citicoline. The findings demonstrated a significantly higher level of HSP70 in patients compared with healthy individuals, supporting its role as a marker of oxidative and stress-related neuronal injury. In contrast, the GRIN2B marker did not differ significantly between groups before treatment, although a tendency toward higher values in patients was observed. After ten days of combined therapy, neither marker showed a statistically significant group-level change, which may reflect substantial inter-individual variability, insufficient treatment duration, or the need for larger sample sizes to detect subtle neurobiological effects. Despite the lack of a significant difference in baseline values, the GRIN2B marker exhibited a strong prognostic ability in identifying individuals who demonstrated a favorable biochemical response to treatment, suggesting potential utility in patient stratification and monitoring early therapeutic effects. HSP70 demonstrated limited predictive value over the short therapeutic interval, which may reflect the complexity of its regulation and the need for longer observation windows. Overall, the results indicate that these circulating proteins may complement existing clinical tools for assessing disease mechanisms in primary open-angle glaucoma. HSP70 may serve as an indicator of oxidative stress and retinal ganglion cell injury, while the GRIN2B marker may hold promise as an early indicator of treatment response. Further research is required to determine their stability over time, relevance in different disease stages, and suitability for integration into clinical decision-making.